1976
DOI: 10.1037/0022-3514.33.6.755
|View full text |Cite
|
Sign up to set email alerts
|

Verbal imagery and connotation as memory-induced mediators of aggressive behavior.

Abstract: Three studies investigated the effects of an information-processing variable (imagery-concreteness) on susceptibility to aggressive stimulation. Study 1 (n=83) results indicated that subjects' rating of imagery level and aggressive connotation for words can be manipulated independently. In study 2 (n=64), manipulations of verbal connotation and verbal imagery indicated that imagery level but not aggressive connotation significantly influenced the delayed recall of the verbal material. In Study 3 (n=60), males … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1976
1976
1998
1998

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…As noted earlier, the weapons effect on aggressive behavior is well established. Similarly, merely memorizing aggressive words increases later aggressive behavior (Turner & Layton, 1976). Furthermore, decades of research on the effects of viewing television violence have yielded substantial links to subsequent aggressive behavior (e.g., Huesmann & Miller, 1994).…”
Section: A Missing Linkmentioning
confidence: 99%
“…As noted earlier, the weapons effect on aggressive behavior is well established. Similarly, merely memorizing aggressive words increases later aggressive behavior (Turner & Layton, 1976). Furthermore, decades of research on the effects of viewing television violence have yielded substantial links to subsequent aggressive behavior (e.g., Huesmann & Miller, 1994).…”
Section: A Missing Linkmentioning
confidence: 99%
“…We have suggested that the impact o f aggressive cues is determined by factors such as the meaning attached t o them, the degree t o which they are associated with reward and punishment, and individual differences in people's experience with firearms. Turner and Layton (1976) and Turner and Goldsmith (1976) have proposed an information processing and memory analysis that provides an additional mechanism by which aggressive stimuli such as firearms could facilitate aggressive behavior. Not only may people learn an aggressive meaning to firearms because of the common association between firearms and aggressive behavior, but the firearms may serve as retrieval (or reminder) cues for earlier aggressive episodes.…”
Section: Memory and Information Processing Of Aggressive Cuesmentioning
confidence: 99%
“…Recently, Collins (1982), Huesmann (1982), and Turner (Turner & Layton, 1976;Turner & Fenn, 1979) attempted to connect the effects of television violence viewing more closely to theorizing in cognitive psychology. They have suggested that aggressive problemsolving strategies may be associated with specific cues in an aggressive film and retrieved when those cues or similar cues are present.…”
mentioning
confidence: 99%